Some Notes on Binding Magic (maʾǝsärä ǝgr) in Ethiopia - Mulugetta, Meley (Aethiopica, 2015)
Ethiopian magical texts abound in their inclusion of magical formulae for binding slaves (maʾǝsärä ǝgr, ‘the tying of feet’), used with the intention of preventing, usually a slave, from running away. This paper will embark on a description of binding magic, the context of their uses and highlight the role of the däbtära, whose ‘in betwixt’ status enables him to cross rigid boundaries of traditional power structures in Christian Ethiopian culture.